2007
DOI: 10.2165/00002018-200730100-00149
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Antidepressant Use and Disturbances in Glucose Homeostasis: Evidence from Spontaneous Reports

Abstract: Objectives Depression is common in patients with diabetes, and the use of antidepressants may impair glycaemic control. We assessed the association between antidepressant use and hyper-and hypoglycaemia. Methods Based on spontaneous reports listed in the World Health Organization (WHO) Adverse Drug Reaction Database, a case-control study was conducted. The study base consisted of all adverse drug reactions (ADRs) ascribed to antidepressants, antipsychotics and benzodiazepines between 1969 and 2005. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 10 publications
3
34
0
1
Order By: Relevance
“…In particular, clozapine and olanzapine, which have the highest affinity for H1 receptor, were the antipsychotics associated with the highest weight gain. In more recent years, Derijks et al, employing the described pharmacodynamic classification for antidepressants, found higher fasting glucose levels in patients taking antidepressants with high antihistaminergic activity (Derijks et al 2008a). A classification of antidepressants based on pharmacological profiles is supported by other findings that explain the neurobiological basis of anti-H1 induced weight gain: an experimental study found that 4 weeks of treatment with amitryptiline and mirtazapine led to an increase in leptin plasma levels and weight gain, while treatment with paroxetine and venlafaxine did not (Schilling et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, clozapine and olanzapine, which have the highest affinity for H1 receptor, were the antipsychotics associated with the highest weight gain. In more recent years, Derijks et al, employing the described pharmacodynamic classification for antidepressants, found higher fasting glucose levels in patients taking antidepressants with high antihistaminergic activity (Derijks et al 2008a). A classification of antidepressants based on pharmacological profiles is supported by other findings that explain the neurobiological basis of anti-H1 induced weight gain: an experimental study found that 4 weeks of treatment with amitryptiline and mirtazapine led to an increase in leptin plasma levels and weight gain, while treatment with paroxetine and venlafaxine did not (Schilling et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ki is the concentration of the ligand in which the receptor is occupied for 50 % by the ligand; thus, the lower the value of Ki, the higher is the affinity of the ligand for the receptor. Values of Ki for all antidepressants were mainly obtained from Derijks et al, which derived Ki values from the Psychoactive Drug Screening Program (PDSP) Ki database, employing not only Ki values coming from experiments with cloned human cell lines but also human receptors from the brain tissue, (frontal) cortex, choroids plexus tissue, striatum tissue, cortical membranes, and platelets (Derijks et al 2008b). Ki value for the antidepressant trimipramine was directly taken from the PDSP database: the value had been obtained from human cortical membranes.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antidepressants such as selective serotonin reuptake inhibitors (SSRIs), including paroxetine, are commonly used in diabetic patients. Paroxetine improved glucose metabolism and insulin sensitivity via alleviating depression [10,11] , although antidepressant use that was associated with disturbances in glucose homeostasis has been reported [12,13] .…”
Section: Introductionmentioning
confidence: 99%